Cellular components of tumor microenvironment: understanding their role in lymphatic metastasis of tumors - Wang, Ziyi; Li, Zehui; Sun, Xiangyu; Men, Wanfu; Xu, Yan (Frontiers in Pharmacology, 2024)
Metastasis is the leading cause of cancer-related death in cancer patients. Tumor cells primarily spread through the hematogenous and lymphatic system. The underlying mechanisms of hematogenous metastasis have been well described over the past few decades. However, the understanding of the molecular mechanisms involved in lymphatic metastasis is still at an early stage. Tumor microenvironment (TME), primarily consisting of T cells, B cells, tumor-associated macrophages, neutrophils, and cancer-associated fibroblasts, has been implicated in the development of lymphatic metastasis. Recent studies have been reported that the dynamic and complex interplay between these cellular components of TME has great effects on lymphatic metastasis. Here, we discussed the paradoxical roles of these cellular component within the TME during lymphatic metastasis, as well as potential therapeutic opportunities to re-educate these cells within the TME to have anti-tumorigenic effects.